2019
DOI: 10.1111/jcal.12416
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of adaptive versus non‐adaptive learning with digital educational games

Abstract: Digital educational games are typically used for the training of academic skills.Given the heterogeneity in children's prior knowledge and learning pace in classrooms, especially educational games with integrated adaptivity are promising. Adaptive educational games are considered superior to non-adaptive educational games, because they constantly assess children's performance, and accordingly adapt the difficulty of the tasks corresponding to the children's individual level. However, empirical evidence with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 50 publications
(51 reference statements)
4
44
0
3
Order By: Relevance
“…However, the current study does not indicate a significant effect of adapting game levels to fit learners' needs relative to either game enjoyment or test performance. This result is consistent with the findings of Vanbecelaere et al (2019) who similarly reported no difference in game‐based learning as a function of adaptivity. It also supports other findings that a computer‐based learning environment that makes navigation decisions for students (i.e.…”
Section: Summary and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the current study does not indicate a significant effect of adapting game levels to fit learners' needs relative to either game enjoyment or test performance. This result is consistent with the findings of Vanbecelaere et al (2019) who similarly reported no difference in game‐based learning as a function of adaptivity. It also supports other findings that a computer‐based learning environment that makes navigation decisions for students (i.e.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…Black & Deci, 2000; Vansteenkiste, Simons, Lens, Sheldon, & Deci, 2004). For instance, Vanbecelaere et al (2019) compared the effectiveness of an adaptive versus a non‐adaptive educational game on kindergarten students' cognitive and non‐cognitive gains. Results showed significant learning gains in general but no difference between conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive computer games could evaluate students’ performance, and thus adapt corresponding levels of difficulty to students. However, they failed to greatly improve the motivation of children (Vanbecelaere et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of adaptivity has been put forward as a promising feature to train particular skills more effectively and to reduce MA (Klinkenberg, Straatemeier, & Van Der Maas, 2011; Sampayo‐Vargas, Cope, He, & Byrne, 2013; Vanbecelaere et al , 2019). A learning environment is adaptive “if it is capable of monitoring the activities of its users, interpreting these on the basis of domain‐specific models, inferring user requirements and preferences out of the interpreted activities, appropriately representing these in associated models; and finally, acting upon the available knowledge on its users and the subject matter at hand, to dynamically facilitate the learning process” (Paramythis & Loidl‐Reisinger, 2003, p. 182).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous research has shown that specific features of digital games might enhance learning, such as automatically generated exercises, immediate feedback (O’Rourke, Main, & Hill, 2017), interaction between the system and the learner, concrete representations, and an attractive narrative (Ronimus, Kujala, Tolvanen, & Lyytinen, 2014). Recently, there has been increased attention for the integration of adaptivity which facilitates the alignment of exercise difficulty to the child’s ability (Hooshyar et al , 2019; Vanbecelaere et al , 2019).…”
Section: Introductionmentioning
confidence: 99%